2016
DOI: 10.1016/j.cya.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Global financial crisis, ownership and bank profit efficiency in the Bangladesh's state owned and private commercial banks

Abstract: Global financial crisis, ownership and bank profit efficiency in the Bangladesh's state owned and private commercial banks Crisis financiera global, propiedad y eficiencia de las ganancias en los bancos comerciales estatales y privados en Bangladesh

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
2
47
1
1
Order By: Relevance
“…That said, arguably Islamic banks in Indonesia are more affected by financial crisis. Kamarudin et al (2016b) concluded that the impact of the financial crisis on the level of banking efficiency actually occurred after the crisis, not during a crisis, due to the time lag or time lapse until the impact begins to be felt in the financial and banking industries. The results are relevant to Hidayati et al (2017) that Islamic banks and Islamic business units in Indonesia did not function efficiently in its intermediation.…”
Section: Discussionmentioning
confidence: 99%
“…That said, arguably Islamic banks in Indonesia are more affected by financial crisis. Kamarudin et al (2016b) concluded that the impact of the financial crisis on the level of banking efficiency actually occurred after the crisis, not during a crisis, due to the time lag or time lapse until the impact begins to be felt in the financial and banking industries. The results are relevant to Hidayati et al (2017) that Islamic banks and Islamic business units in Indonesia did not function efficiently in its intermediation.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows a positive and significant relationship between inflation rate and the performance of MFIs as more borrowers still can be reached even in a high inflationary environment. In the study of Kamarudin et al (2016), they also found that inflation rate has a positive relationship with the profitability of both small and big banks. When the inflation rate is increased, banks will impose high servicing charges on their customers.…”
Section: Literature Reviewsmentioning
confidence: 93%
“…The impacts of inflation rate (lnINF) are significantly positive at 1% level for social efficiency in all models, and Model 4 is specifically for financial efficiency. The number of borrowers increases even though the interest rate is higher because they anticipate much higher inflation in future that will lead to much higher interest rates (Bibi et al, 2018;Kamarudin et al, 2016). Besides, the higher interest rate during inflation may impact borrower's incentives to default.…”
Section: Determinants Of Efficiency Level In Mfismentioning
confidence: 99%
“…We used the same inputs and output variables to determine the efficiency under the SFA approach. Note that we included year dummies in the SFA estimation to control for time effects, and used a truncated normal distribution assumption for the inefficiency term (For a more detailed discussion of the estimation process, see (Baik et al, 2013;Ali, 2015;Kamarudin et al, 2016;Nabi et al, 2019;Samad, 2019). Table 1 presents the summary statistics of our input, output and efficiency measures.…”
Section: Input and Output Variables And Estimation Of Efficiencymentioning
confidence: 99%